Réponses

Meilleure réponse !
2014-10-19T10:34:30+02:00
2014-10-19T10:39:45+02:00
A= 3(2x-1)-5(1-x)                                                                                                                            =3*2x +3*(-1)+ 3*(-5) +3*(-1)                                                                                                    =6x-3x-15-3                                                                                                                                  = 3x -18     
voila la réponse